2015
DOI: 10.1111/ecog.01328
|View full text |Cite
|
Sign up to set email alerts
|

The effects of individual tree species on species diversity in a tropical dry forest change throughout ontogeny

Abstract: Understanding how diversity is maintained in species‐rich communities, such as tropical forests, remains a challenge in ecology. Recent work suggests that the controversy between competing theories could be better resolved by considering the spatial scale at which different processes rule community assembly. Here we use individual species–area relationships (ISAR) to evaluate the spatial organization of tree diversity around individuals of different species in a completely‐mapped tropical dry forest in south E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 52 publications
2
35
2
Order By: Relevance
“…For example, in a tropical dry forest in Ecuador, Espinosa et al. () found evidence of facilitation but that site has a more pronounced dry season and receives substantially less precipitation than the driest site in our study (ca. 650 mm/yr vs. ca.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…For example, in a tropical dry forest in Ecuador, Espinosa et al. () found evidence of facilitation but that site has a more pronounced dry season and receives substantially less precipitation than the driest site in our study (ca. 650 mm/yr vs. ca.…”
Section: Discussioncontrasting
confidence: 58%
“…It is also possible that the range of the gradient studied here is not wide enough to observe positive interactions in the dry site. For example, in a tropical dry forest in Ecuador, Espinosa et al (2016) found evidence of facilitation but that site has a more pronounced dry season and receives substantially less precipitation than the driest site in our study (ca. 650 mm/yr vs. ca.…”
Section: Crowding Effects Vary Across the Gradientcontrasting
confidence: 50%
“…), one of the last remnants of lowland tropical dry forests in the world and one of the few remaining habitats for the Pacific horned frog (Ortiz et al, 2013). The annual precipitation average is 676 mm, but with large variations between years (between 65 and 2647 mm, Huaquillas meteorological station, 45 years records), and distributed almost exclusively during the four months of the wet season (January-April; 515 mm on average), while the dry season has at least 4 months with less than 10 mm monthly precipitation (Espinosa et al, 2016). Because of the extended dry season, there are no permanent water habitats, even longer-lasting ponds drying up in a few weeks.…”
Section: Study Species and Locationmentioning
confidence: 99%
“…), local dispersal events (Hubbell ; Hardy & Sonké ), facilitation (Espinosa et al . ), topography and the availability of microsites with favourable conditions for survival up to maturity (Hay et al . ; Costa & Santos ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spatial repulsion between adults and juveniles may be a response to environmental heterogeneity (Espinosa et al . ), since different stages have different environmental requirements. However, despite the fact that the detection of DDM can be masked by the influence of habitat heterogeneity, DDM is still the predominant regulator of the spatial structure of most tropical trees, especially of abundant species (Zhu et al .…”
Section: Introductionmentioning
confidence: 99%